EMC. Hématologie ([Éditions scientifique et médicales Elsevier SAS], 2004)
" ... covers all fields of hematology comprising cytogenetics, immunology, molecular hematology and hemostasis"--Publisher information page.
Keywords: Hematology : Periodicals; Blood : Diseases : Periodicals; Hematology; Blood : Diseases; Hématologie; Maladie du sang